2007
DOI: 10.1007/s11892-007-0070-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathy associated with prediabetes: What is new in 2007?

Abstract: Length-dependent polyneuropathy has long been recognized as a frequent complication of diabetes. A decade of observational and epidemiologic studies support the concept that intermittent hyperglycemia or insulin resistance associated with prediabetes may be sufficient to damage distal nerves. Features of the metabolic syndrome have been implicated as independent neuropathy risk factors in large population-based studies of diabetic patients. Preferential injury to small unmyelinated nerves is suggested by promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 41 publications
1
26
0
1
Order By: Relevance
“…In particular, we have shown that maladaptive dendritic spine plasticity occurs on WDR neurons, which can contribute to adversely altered sensory processing associated with chronic pain (Tan et al, 2008(Tan et al, , 2009a. Neuropathic pain develops progressively over time in diabetic animal models and chronic diabetes in humans (Malcangio and Tomlinson, 1998;Marchettini et al, 2004;Singleton and Smith, 2007;Fischer et al, 2009). To determine whether diabetic neuropathic pain associated with changes in dendritic spine morphology, we first analyzed dendritic spines from spinal cord tissue collected 4 weeks after STZ or control injection ( Fig.…”
Section: Dendritic Spines Remodel On Dorsal Horn Neurons In Experimenmentioning
confidence: 99%
“…In particular, we have shown that maladaptive dendritic spine plasticity occurs on WDR neurons, which can contribute to adversely altered sensory processing associated with chronic pain (Tan et al, 2008(Tan et al, , 2009a. Neuropathic pain develops progressively over time in diabetic animal models and chronic diabetes in humans (Malcangio and Tomlinson, 1998;Marchettini et al, 2004;Singleton and Smith, 2007;Fischer et al, 2009). To determine whether diabetic neuropathic pain associated with changes in dendritic spine morphology, we first analyzed dendritic spines from spinal cord tissue collected 4 weeks after STZ or control injection ( Fig.…”
Section: Dendritic Spines Remodel On Dorsal Horn Neurons In Experimenmentioning
confidence: 99%
“…77,[84][85][86] Insulin resistance by itself is a risk factor for neuropathy, retinopathy and renal disease as well as death due to myocardial infarction and stroke. [87][88][89][90][91][92][93] The risk of cardiovascular disease is increased before glucose levels reach the "diabetic threshold." 94 And in some studies, glucose control does not decrease myocardial infarction.…”
Section: Insulin Resistancementioning
confidence: 99%
“…Insulin resistance the characteristic finding in NAFLD and metabolic syndrome has been shown in non-liver settings, such as polycystic ovary syndrome [34] and obstructive sleep apnoea [33] to be associated with autonomic dysfunction, although a lack of association between autonomic symptom burden and HOMA found in the current study might argue against this. Prediabetes has been associated with autonomic dysfunction [39], although none of the NAFLD patients in this study had diabetes, it may be that NAFLD subjects with the fatigue phenotype are those at increased risk of developing diabetes over longer-term follow up. Further work is needed to explore more fully the long-term implications of autonomic dysfunction in NAFLD.…”
Section: Discussionmentioning
confidence: 61%